Postoperative pain assessment in hospitalised patients: National survey and secondary data analysis. (November 2016) - Hoogervorst-Schilp, J.; van Boekel, R.L.M.; de Blok, C.; Steegers, M.A.H.; Spreeuwenberg, P.; Wagner, C.
Abstract: Background: Measuring pain is important for the adequate pain management of postoperative patients. The actual compliance with pain assessment in postoperative patients after implementation of a national safety program is unknown. Objectives: The aim of this study is to examine the compliance with pain assessment in postoperative patients after implementation of a national safety program, according to the national quality indicators for pain assessment in postoperative patients. Furthermore, organisational factors associated with this compliance were determined. Study design: In this study, two data sources were used: 1) data from an evaluation study of the Dutch Hospital Patient Safety Program; and 2) data from a questionnaire survey. Methods: The compliance with two different pain process indicators was determined: 1) 3 pain measurements a day, all three full days after surgery; and 2) ≥1 pain measurement a day, all three full days after surgery. Multilevel logistic regression analysis was used to investigate the association between organisational factors in hospitals and compliance with pain process indicators. Results: Data of 3895 patient records from 16 hospitals was included in this study. In 12% of the postoperative patients, pain was measured 3 times a day, all three full days after surgery. In 53% of the postoperative patients, pain was measured ≥1 time a day, all three full days after surgery. Compliance was highest in general hospitals compared to tertiary teaching and academic hospitals, and was statistically significantly higher at the surgery and surgical oncology department compared to the other departments. Conclusions: Low compliance was shown with pain assessment in postoperative patients, according to the process indicator pain after surgery in Dutch hospitals. This suggests that the implementation of measuring pain in hospitals is still insufficient.